Critique of the Arabic Translation Strategies of Verbo-Pictorial Gendered Metaphor: Doris Lessing's The Cleft - Sabra, Nour Elhoda (International Journal of Linguistics and Translation Studies, 2023)
This article is mainly concerned with the strategies employed in translating verbo-pictorial gendered metaphor when used as a literary work cover. It focuses on the translation strategies employed by Arab translators in translating the cover of Doris Lessing's novel The Cleft. It raises the questions of to what extent translating a verbo-pictorial gendered metaphor employed as a literary work cover may clarify and elucidate nontraditional new images in different cultures. The article also emphasizes how a verbo-pictorial gendered metaphor plays a role in structuring gender relation new images. The article argues that the translation of gendered metaphors that appeared in feminist literary works invites different translation strategies when it is translated from English into Arabic.